2009
DOI: 10.1186/1742-6405-6-21
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral treatment adherence and its determinants in Sub-Saharan Africa: a prospective study at Yaounde Central Hospital, Cameroon

Abstract: BackgroundWith African health-care systems facing exploding demand for HIV care, reliable methods for assessing adherence and its influencing factors are needed to guide effective public-health measures. This study evaluated individual patient characteristics determining antiretroviral treatment (ART) adherence and the predictive values of different measures of adherence on virological treatment failure in a cohort of patients in a routine-care setting in Cameroon.MethodsLongitudinal study over 6-months follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
91
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 28 publications
10
91
6
Order By: Relevance
“…This can be surely attached to their failing immune system increasing the patient's vulnerability and the fact that IgG-antibodies last longer than IgM-antibodies. It is therefore possible most of the toxoplasmosis cases in HIV/AIDS are due to a reactivated infection (18). A 3/5 ratio of male to females (p>0.05) did not provide enough statistic evidence that positivity of toxoplasma antibodies is not sex dependent.…”
Section: Discussionmentioning
confidence: 90%
“…This can be surely attached to their failing immune system increasing the patient's vulnerability and the fact that IgG-antibodies last longer than IgM-antibodies. It is therefore possible most of the toxoplasmosis cases in HIV/AIDS are due to a reactivated infection (18). A 3/5 ratio of male to females (p>0.05) did not provide enough statistic evidence that positivity of toxoplasma antibodies is not sex dependent.…”
Section: Discussionmentioning
confidence: 90%
“…The respondents of more than 40 years of age were significantly less likely to adhere ART in this study although several studies reported that there is no consistent correlation between demographic characteristics and level of adherence. 24,25 Many potentially debilitating adverse effects of ART have also been shown to contribute to irregular taking of the drugs and deliberately stopping of medication by some patients. 26 The results of current study revealed that the side effect of ART was not associated with ART adherence.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] Of the few studies that have estimated the extent of TIs (including loss to follow-up; LTFU) since the SMART study; none compared pre-2006 to 2006 onwards, none measured the impact of the TI on HIV viral load or CD4 count, all defined TI using an interval of less than 4 weeks and thus included interruptions where viral load may not have been high enough to result in HIV transmission, and all were conducted in Africa or the United States. [20][21][22][23][24] The aim of this study was to investigate the incidence, frequency of TIs and LTFU pre and post 2006, risk factors for TI, and the impact of TI on plasma HIV viral load across 13 countries covering both high and low-income settings in Asia and the Pacific.…”
mentioning
confidence: 99%